2021
DOI: 10.1126/sciadv.abc5267
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the acquired vulnerability of cisplatin-resistant tumors with a hypoxia-amplifying DNA repair–inhibiting (HYDRI) nanomedicine

Abstract: Various cancers treated with cisplatin almost invariably develop drug resistance that is frequently caused by substantial DNA repair. We searched for acquired vulnerabilities of cisplatin-resistant cancers to identify undiscovered therapy. We herein found that cisplatin resistance of cancer cells comes at a fitness cost of increased intracellular hypoxia. Then, we conceived an inspired strategy to combat the tumor drug resistance by exploiting the increased intracellular hypoxia that occurs as the cells develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…S1) and characterized with ESI–MS (Additional file 1 : Fig. S2) [ 24 ]. HSA is the most abundant protein in the human bloodstream [ 25 , 26 ], which is widely used as drug carriers [ 27 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…S1) and characterized with ESI–MS (Additional file 1 : Fig. S2) [ 24 ]. HSA is the most abundant protein in the human bloodstream [ 25 , 26 ], which is widely used as drug carriers [ 27 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, it has been shown that chemotherapy can modulate pro-survival pathways like increasing the expression of drug efflux pumps, apoptosis defects, DNA adduct tolerance, cellular detoxification, and inducing a hypoxic environment [ 25 ] . While the metabolic effects of hypoxia will be discussed in more detail below, Chen et al [ 26 ] have taken advantage of intracellular hypoxia in cisplatin-resistant cells and created a hypoxia-amplifying DNA repair-inhibiting (HYDRI) nanomedicine. HYDRI specifically targeted cancer cells because of their drug-induced hypoxic environment, and then released its payload of hypoxia-activatable chemotherapeutic tirapazamine.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…HYDRI specifically targeted cancer cells because of their drug-induced hypoxic environment, and then released its payload of hypoxia-activatable chemotherapeutic tirapazamine. In this way, previous studies which determined upregulated pathways in cisplatin resistance could be used to create a smarter therapy that bypassed drug efflux pumps, induced a unique DNA damage profile, and relied on the inevitable hypoxic environment created by cisplatin resistance to target these drug-refractory models [ 26 ] .…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…2016 Dec 12; 55 (50):15564–15568). Recently, researchers proposed a novel nano-chemotherapy strategy that is to build a liposome nanodrug containing glucose oxidase (GOx), tirapazamine (TPZ), and platinum (IV) prodrug ( Chen J. et al, 2021 ). The nanodrug can not only be fully utilized but also further aggravate intracellular hypoxia of cisplatin-resistant tumor cells, thus fully activating TPZ drug activity.…”
Section: Nanomaterials Therapeutics Overcome Drug Resistancementioning
confidence: 99%
“… Schematic illustration of the GOx/TPZ@Lipo-Pt nanomaterial and hypoxia-induced reversal of cisplatin resistance. Reproduced with permission ( Chen J. et al, 2021 ). Copyright 2021, American Chemical Society.…”
Section: Nanomaterials Therapeutics Overcome Drug Resistancementioning
confidence: 99%